Descriptive Characterization of Psycho-Trauma, Psychological Distress, and Post-traumatic Stress Disorder among Children and Adolescent Internally Displaced Persons in Kaduna, Nigeria - Sheikh, Taiwo Lateef; Mohammed, Abdulaziz; Eseigbe, Edwin; Adekeye, Tosin; Nuhu, Folorunsho Tajudeen; Lasisi, Modupe; Muhammad, Asiya; Sulaiman, Zainab Titilope; Abdullateef, Aishatu Abubakar; Hayyatudeen, Nafisatu; Akande, Yusuf (Frontiers in Psychiatry, 2016)
Background A post election violent conflict in northern Nigeria in April 2011 resulted in 800 deaths and 65,000 displaced people leading to setting up of camp for Internally Displaced Persons (IDPs). We set out to determine the prevalence and pattern of psycho-traumatic stressful life events, psychological distress and PTSD among children and adolescents IDPs. Methods A descriptive cross sectional study of 73 child and adolescent IDPs selected by total sampling. We used the Stressful Life Event checklist to measure conflict-related trauma and Reaction of Adolescents to Traumatic Stress to measure post trauma reaction of children and adolescents. Hopkins Symptoms Checklist 37 for Adolescents measured psychological distress associated with trauma in the participants. Diagnostic Interview Schedule for Children (C-DISC) used to make a diagnosis of definitive Post Traumatic Stress Disorder (PTSD). We described the most frequently occurring psycho-traumatic events and psychological distress. We also calculated the prevalence of probable and definitive PTSD Results Out of 73 respondents, three (4.1%) participants had probable PTSD, and two (2.7%) had definitive PTSD. The mean score of the children/adolescent IDPs on HSCL-37A and RATS were 44.7 (SD = 6.3) and 31.9 (SD = 5.7) respectively. The most frequently occurring psychological distress among female participants was suddenly scared for no reason 7 (19.5%) and, becoming angry easily and feeling fearful 5 (13.9%). The average score and standard deviation of female participants 34.3 (5.2) and 15.1 (3.1) were higher than that for males 29.6 (3.3) and 14.4 (2.2) for depressive and anxiety sub-scale of HSCL-37A respectively Conclusion We concluded that children/adolescent IDPs were exposed to psycho-trauma following post election violent conflict and developed psychological distress. However the low prevalence of psychological distress and PTSD suggested that living with parents and psychosocial intervention provided could have led to much lower morbidity.